Household Sustainable Consumption Intention - Ab. Halim, Roslilee; Chuah, Soo-Cheng (Information Management and Business Review, 2023)
Household consumption could hurt the environment. What we collectively choose and consume on a day-to-day basis determines what’s left for future generations. As household consumption is one of the largest activities in an economy, sustainable consumption is an important key to achieving sustainability goals. Improvement in the role of individual citizens in society, concerning sustainability is vital for a better future in all aspects of the environment, society and economy. The purpose of this article is to examine how education, sustainable awareness and attitude, as well as social influence impact the intention to consume sustainably among households. The method used is quantitative where cross-sectional data was collected through an online self-administered questionnaire in which a convenience sampling method was applied to 151 respondents. The data was analyzed using partial least square structural equation modeling (PLS-SEM) by utilizing SmartPLS3 software. The findings suggest that social influence and sustainable awareness and attitude had a significant influence on the intention toward sustainable consumption among households. Education however was found to be insignificant and not sufficient as the predictor in this study. Implications for policymakers and the directions of future research are proposed.